Implementasi Kebijakan Kinerja dan Komunikasi Interpersonal Pegawai pada Kantor Kementerian Agama Kota Bengkulu - Reza Saputra Wardama; Hurian Kamela (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Employee performance is the result of a combination of ability and motivation. The importance of employee performance lies in the fact that each individual's performance contributes to the organization's overall performance, which can determine whether the organization is successful. Then, in its implementation, interpersonal communication also becomes an important factor in employee performance. This research aims to determine how the Office of the Ministry of Religion of Bengkulu City implements employee performance and interpersonal communication policies. A qualitative approach was used in this research. The findings of this research indicate that the Bengkulu City Ministry of Religion has implemented performance policies to improve employee performance. With clear and measurable policies, the Ministry of Religion hopes to encourage its employees to work more professionally and efficiently. However, there are still problems in implementation, such as the absence of employee performance evaluation. One of the important factors in increasing productivity at the Bengkulu City Ministry of Religion Office is effective interpersonal communication, which in turn greatly influences employee happiness at work. A cheerful work atmosphere, inspired workers, and stronger bonds between coworkers are the results of effective communication. When there is clear and constant communication between managers and staff, workers feel appreciated and inspired to do their best. A happy and productive work atmosphere relies heavily on effective communication.